Enhancing System Security Using Cryptographic Algorithms for Student Attendance Management - Tri Muji Waluyo; Derry Setiawan; Yuni Handayani; Taufik Hidayat; Dian Novitaningrum (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
In educational institutions, the accuracy and security of student attendance records are critical for administrative processes, performance evaluation, and compliance monitoring. However, traditional student absence systems are vulnerable to data breaches, unauthorized access, and manipulation, which can compromise the integrity of attendance data. This project proposes a secure student absence management system that leverages modern cryptographic algorithms to enhance data protection and system integrity. By integrating encryption techniques such as [e.g., AES or RSA], the system ensures that attendance data is securely stored, transmitted, and accessed only by authorized personnel. The proposed system aims to prevent data tampering, unauthorized modifications, and impersonation, thereby improving overall system reliability. A comparative analysis is conducted to evaluate the effectiveness of the chosen cryptographic algorithm in terms of performance, scalability, and security. The results demonstrate that the implementation of cryptographic methods significantly improves the confidentiality, integrity, and availability of student attendance data, making the system more robust and trustworthy.